ANÁLISIS COMPARATIVO DE LAS POLÍTICAS MACROECONÓMICAS DE SINGAPUR Y PERÚ DE LOS ÚLTIMOS 20 AÑOS: UNA PROPUESTA - Sanchez Soto, Ruben Gomez (2021)
The results achieved by Singapore in terms oflevels of development are recognized by differentInternational organizations. Recently, WordEconomic Forum (2019) published its global report oncompetitiveness noting that Singapore has surpassedto many countries that previously held the firstpositions in several of the factors that, taken together,generate the global index of competitiveness. for thisreason, it was decided to make a comparative analysis betweenthe development of Singapore and Peru. Depending on the scenariosof each country, variables are presented that would supportthis difference, and according to this, a set ofmacroeconomic policies for its implementationin Peru. Finally, as a complement to the presentarticle, a simulation model is explained insystem dynamics, referring to the improvement of thequality of democracy, which would be correlatedwith adequate macroeconomic policies that would beimplemented in Peru.